The Association of Cigarette Smoking With High-Frequency Heart Rate Variability: An Ecological Momentary Assessment Study. Issue 9 (November 2017) - Bodin, Fernando; McIntyre, Kathleen M.; Schwartz, Joseph E.; McKinley, Paula S.; Cardetti, Caitlyn; Shapiro, Peter A.; Gorenstein, Ethan; Sloan, Richard P.
ABSTRACT: Objective: Evidence from both laboratory and observational studies suggests that acute and chronic smoking leads to reduced high-frequency heart rate variability (HF-HRV), a measure of cardiac vagal regulation. We used ecological momentary assessment (EMA) to study the effect of smoking on concurrent HF-HRV in a trial measuring the effects of hostility reduction and compared 24-hour HF-HRV in smokers and nonsmokers. Method: Ambulatory electrocardiogram data were collected before randomization from 149 healthy individuals with high hostility levels (20–45 years, body mass index ⩽ 32 kg/m 2 ) and paired with concurrent EMA ratings of smoking and physical position during waking hours. A multilevel mixed model was estimated associating ln(HF-HRV) from smoking status (between-person factor) and person-centered momentary smoking (within-person factor, treated as a random effect), adjusting for momentary physical position, medication use, and consumption of alcohol and caffeine. Results: Thirty-five smokers and 114 nonsmokers provided both EMA and HF-HRV data. Within smokers, ln HF-HRV was reduced by 0.31 millisecond 2 ( p = .04) when participants reported having recently smoked cigarettes, compared with when they had not. The 24-hour HF-HRV was significantly lower in smokers (M [SD] = 5.24 [0.14] milliseconds 2 ) than nonsmokers (5.63 ± 0.07 milliseconds 2, p = .01). Conclusions: In healthy smokers with high hostility levels used as their own controls during daily living, smoking acutely reduced HF-HRV. HF-HRV was also reduced in smokers as compared with nonsmokers. Although limited by a small sample of individuals with high hostility levels, these findings nonetheless provide additional evidence that cardiac vagal regulation is lowered by cigarette smoking, which may be one of the numerous pathophysiological effects of smoking.